2023
DOI: 10.1099/mic.0.001292
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane substrates of type three secretion system injectisomes

Abstract: The type three secretion system injectisome of Gram-negative bacterial pathogens injects virulence proteins, called effectors, into host cells. Effectors of mammalian pathogens carry out a range of functions enabling bacterial invasion, replication, immune suppression and transmission. The injectisome secretes two translocon proteins that insert into host cell membranes to form a translocon pore, through which effectors are delivered. A subset of effectors also integrate into infected cell membranes, enabling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 130 publications
(243 reference statements)
0
2
0
Order By: Relevance
“…These regions include the highest level of sequence identity among the translocon proteins. 48 We have previously shown that replacement of these TMDs, even by TMDs from other TMD-containing secreted proteins, impairs post-secretion function of these translocon components and prevents the formation of functional pores. 35 Here, we considered whether the EspB TMD-exchanged variants were defective in terms of their ability to dimerize and integrate into EspD oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…These regions include the highest level of sequence identity among the translocon proteins. 48 We have previously shown that replacement of these TMDs, even by TMDs from other TMD-containing secreted proteins, impairs post-secretion function of these translocon components and prevents the formation of functional pores. 35 Here, we considered whether the EspB TMD-exchanged variants were defective in terms of their ability to dimerize and integrate into EspD oligomers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their role in the translocation of Yops, YopD and LcrV may have additional roles in modifying the host response to infection as both YopD and LcrV have been found to localize to the host cell cytoplasm [ 127 , 128 ]. Furthermore, functional homologs of YopB, YopD, and LcrV are found in most T3SSs expressed by gram-negative bacteria, where strong evidence supports their direct roles on the host cell response [ 129 ]. Insertion of the translocation pore into host membranes connects the cytoplasm of the two cells, allowing direct injection of effector Yops into the host cytoplasm.…”
Section: T3ss Translocation Porementioning
confidence: 99%